Comparative Investigation of Alliteration in Modern English and Uzbek - Pazilova Nasibaxon Muhammadqosimovna; G’ofurova Gullola Axmadullayevna (Zien Journals, 2022)
This article deals with the study of alliteration in Modern English and Uzbek which is one of the literary devices in both languages. Thus, it discusses specific features and types of alliteration in both languages with examples.
Keywords: Alliteration; Literary Device; Initial Consonant Sounds; Tongue Twisters